Peningkatan Ketrampilan Wartawan Media Siber Menulis Berita Sesuai Tuntutan SEO yang Mematuhi Kode Etik Pers: Improving Cyber Media Journalists' Skills in Writing News in Accordance with SEO Requirements and Complying with the Press Code of Ethics - Sahputra, Dedi; Lubis, Khairunnisa; Fitria, Dilla; Siregar, Trismalia Putri; Siregar, Desi Kartika (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The main problem of the Indonesian Journalists Association of Serdang Bedagai, as a partner in community service activities, is the lack of Search Engine Optimization (SEO) skills and adherence to press law ethics among its members. The purpose of this activity is to equip partners with the skills to produce journalistic products that meet SEO demands while adhering to ethical content and press law standards. The methods used are training, simulation, and monitoring of journalistic products. The training resulted in improved partner skills in producing journalistic products that meet SEO requirements, with ethical content and press law. Journalists became familiar with SEO indicators and paid greater attention to press ethics and legal issues. Furthermore, partner empowerment in management was enhanced through organizational restructuring. The journalists' organization has established a dedicated section to provide a forum for discussion on digital news and to resolve ethical and legal issues among its members.